Flora of Singapore Precursors, 11. A new species of Urophyllum (Rubiaceae) from the Malay Peninsula - Wong, Khoon Meng (Phytotaxa, 2018)
A new species, Urophyllum malayense (Rubiaceae) is described, endemic to the Malay Peninsula (Peninsular Malaysia and Singapore). It has resemblances to Urophyllum trifurcum but differs notably in the extent of inflorescence branching and flower size.